2013
DOI: 10.2172/1220121
|View full text |Cite
|
Sign up to set email alerts
|

The Next Step Toward Widespread Residential Deep Energy Retrofits

Abstract: iv [This page left blank]v

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…An additional set of 70 Central and North-Florida dwellings were energy retrofitted as part of a separate research effort (McIlvaine et al, 2013). These energy upgrades were add-ons to rehabilitation/remodeling projects otherwise being carried out by affordable housing partners in the state of Florida.…”
Section: Affordable Housing Partner Dersmentioning
confidence: 99%
“…An additional set of 70 Central and North-Florida dwellings were energy retrofitted as part of a separate research effort (McIlvaine et al, 2013). These energy upgrades were add-ons to rehabilitation/remodeling projects otherwise being carried out by affordable housing partners in the state of Florida.…”
Section: Affordable Housing Partner Dersmentioning
confidence: 99%
“…Several studies have identified a lack of project financing as a barrier to home upgrades [22,30,37]. However, these and other studies have shown that the majority of projects do not use financing [3,58,59].…”
mentioning
confidence: 99%